2021
DOI: 10.1371/journal.pone.0255177
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the mediating roles of self-directed learning and knowledge management processes between emotional intelligence and learning outcomes in higher education

Abstract: Objective: Drawing on the knowledge-based view and ability-based theories of emotional intelligence (EI), in this study, we investigate the effects of EI on learning outcomes related to academics and administrators in Chinese research universities and we also test the direct association between learning outcomes and creative performance. In addition, we examine the mediating role of self-directed learning (SDL) and knowledge management processes (KMPs) on the relationship between EI and learning outcomes. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 88 publications
(116 reference statements)
1
29
0
1
Order By: Relevance
“…Considerable evidence has suggested that employee creativity can benefit organizational reformation and innovation, competitiveness, effectiveness, and survival ( Nystrom, 1990 ; Zhou, 2003 ; Shalley and Gilson, 2004 ; Sijbom et al, 2018 ), and enhance long-term business success ( Hon, 2012 ). Given the importance of creativity, how to cultivate and maintain employee creativity in organizations has been a hotspot for research on organizational behavior ( Shafait et al, 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence has suggested that employee creativity can benefit organizational reformation and innovation, competitiveness, effectiveness, and survival ( Nystrom, 1990 ; Zhou, 2003 ; Shalley and Gilson, 2004 ; Sijbom et al, 2018 ), and enhance long-term business success ( Hon, 2012 ). Given the importance of creativity, how to cultivate and maintain employee creativity in organizations has been a hotspot for research on organizational behavior ( Shafait et al, 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…The function of an individual’s perceptions and management of their feelings and emotions serves to guide their thinking and actions (Salovey & Mayer, 1990 ). Given the widespread use of EI in the workplace, it has been proved to be conducive to task performance (Chen et al, 2012 ; Law et al, 2008 ), as well as to organizational innovation and creation (Rivera-Vazquez et al, 2009 ; Shafait et al, 2021a , b ).…”
Section: Theoretical Background and Developmentmentioning
confidence: 99%
“…The success largely depends on appropriate implementation of KM processes (Oufkir & Kassou, 2019 ; Wong et al, 2015 ), referring specifically to a set of practices involving knowledge creating, capturing, storing, transferring and using, with an aim to enhance the overall learning outcomes (Barley et al, 2018 ). Given that the source of organizational knowledge are the employees (Nonaka, 1994 ), there have been studies of KM processes’ antecedents related to human characteristics (e.g., Li et al, 2021 ; Shafait et al, 2021a ; Shariq et al, 2019 ; Stoermer et al, 2021 ; Tuan, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOOCs work by offering an online course to students through the internet [ 1 ]. Learning through the internet contains the traditional learning materials that are made accessible online in recorded lectures, course readings, interactive learning modules, online examinations, and online student interaction forums [ 2 , 3 ]. Initially, MOOCs programs were used as open educational resources (OER) and were not designed to offer academic credits.…”
Section: Introductionmentioning
confidence: 99%